2021
DOI: 10.3389/fchem.2021.692168
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dyad Residues His41 and Cys145 Impact the Catalytic Activity and Overall Conformational Fold of the Main SARS-CoV-2 Protease 3-Chymotrypsin-Like Protease

Abstract: Coronaviruses are responsible for multiple pandemics and millions of deaths globally, including the current pandemic of coronavirus disease 2019 (COVID-19). Development of antivirals against coronaviruses, including the severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) responsible for COVID-19, is essential for containing the current and future coronavirus outbreaks. SARS-CoV-2 proteases represent important targets for the development of antivirals because of their role in the processing of viral po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 50 publications
5
72
0
Order By: Relevance
“…From the binding frequency data, active site information for Mpro-ligand complexes over the simulation time showed a similar catalytic dyad of His41 and Cys145 [ 52 ], which has been reported previously [ [53] , [54] , [55] ]. Furthermore, the active site observations for RdRp were supported by other researchers such as Aftab et al, who report that ASP760 and ASP761 can be potential binding sites [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 77%
“…From the binding frequency data, active site information for Mpro-ligand complexes over the simulation time showed a similar catalytic dyad of His41 and Cys145 [ 52 ], which has been reported previously [ [53] , [54] , [55] ]. Furthermore, the active site observations for RdRp were supported by other researchers such as Aftab et al, who report that ASP760 and ASP761 can be potential binding sites [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 77%
“…3 , 4′- O -methylscutellarein ( 4 ) fitted well into the substrate binding site of M pro enzyme with the calculated binding energy of −17.1544 kJ/mol. Previous studies indicated that SARS-CoV-2 M pro catalyzes the cleavage of the protein substrate using the catalytic dyad His41 and Cys145 [ 31 ]. The docking result indicated that the 4′- O -methylscutellarein ( 4 ) is perfectly fitted into the core of the substrate-binding pocket and the catalytic dyad is sequestered from the solvent exposed area to prevent the peptide substrate approaching the active site ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aurasperone A ( 3 ) showed high docking scores (−8.1, −8.0, and −7.8 kcal/mol, Table 1 ) towards the main protease (M pro ), helicase, and RdRp respectively. Visualization of the best docking pose of aurasperone A ( 3 ) against M pro showed the formation of H-bond with Cys-145 amino acid residue ( Figure 3 A and Figure S9A ), which is essential for the enzyme’s catalytic protease activity [ 29 ], in addition to Gly 143 and Ser-144 amino acids present in the active site of the enzyme. Aurasperone A (3) interacted with the ADP site of SARS-CoV-2 RNA helicase through hydrogen bonds with Arg-443 and Glu-540 residues and hydrophobic interaction with several other amino acid residue, as shown in Figure S9C [ 30 ].…”
Section: Resultsmentioning
confidence: 99%